(untitled) (Nepalese Veterinary Journal, 2018)
Ostrich meat is very popular due to its healthy composition thereby increasing its demand globally. Therefore, one study has been made on quality of ostrich meats of different ages at chilled and frozen conditions by targeting product development. Meat samples from two differently aged, 10- and 14-months ostriches were collected and divided into three parts for each type. One part was analyzed immediately, one part was put in chilling at 4°C for 72 hours and next part was put in deep fridge at -20°C for 30 days. Proximate analyses were carried out for moisture (73.98 to 75.22%), protein (21.08 to 22.46%), total fat (2.43 to 3.27%) and total minerals (0.83 to 1.82%). There was subsequent decrement in moisture at cold storage practices, at 72 hours chilling by 1% and one month freezing by 2.3% and there was no significant (?) difference in water content due to the age of bird. The amount of protein was found increasing at chilling, freezing and ageing? total fat was significantly different due to the age as well as meat storage practices and total ash was in decreasing trend in case of chilling and freezing conditions but found no difference due to the age.